Geochemical baseline and multivariate analysis of potentially toxic elements in stream sediments of the Vazante zinc district, Minas Gerais, Brazil - Amarante, Rafael Tarantino; Marques, Eduardo Duarte; Ruchkys, Úrsula Azevedo; Silva-Filho, Emmanoel Vieira; Almeida, Gabriel Soares; Mello, Isadora; Salomão, Gabriel Negreiros (Frontiers in Environmental Science, 2025)
Intense land use, driven by mining and agriculture, promotes the dispersal of elements, including potentially toxic ones (PTEs). This dispersal significantly enhances element concentrations in soils, sediments, and water bodies, thereby altering the natural background values of the environment. The objective of this paper is to employ geochemical mapping alongside multivariate statistical methods to establish the baseline values for the Mining Zinc District situated at the boundary of the São Francisco Craton and Brasília Belt. This will facilitate the assessment of spatial variability and determination of reference values for element concentrations in sediment samples, enabling the differentiation between natural and anthropogenic sources of potentially toxic elements. A geochemical database of 1853 sediment samples were assembled from the São Francisco and Paranaíba watersheds for subsequent ICP-OES and ICP-MS analysis. The baseline values were assessed through 3 distinct methods, while the Factor Analysis was employed as a multivariate statistical technique. The findings reveal that the baseline concentrations of Ni (415 mg.kg−1), Cr (137 mg.kg−1), and Co (106 mg.kg−1) were higher than the Investigation Values of CONAMA Resolution n°454/2012. The factor analysis found 6 main factors that explain 75.1% of the total system variance. It also found 8 major geochemical links between these factors: (1) Al, Cs, Ga, Sn, and V; (2) Co, Mg, Ni, and Zn; (3) Cr, Ni, and V; (4) Cs, K, and Rb; (5) As, and Fe; (6) Cd, Pb, and Zn; (7) LREE, Th, and U; and (8) Ba, P, and Sr.